2019
DOI: 10.1038/s41598-019-45047-9
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analysis of 3D Cardiac Differentiation of Human Induced Pluripotent Stem Cells Reveals Faster Cardiomyocyte Maturation Compared to 2D Culture

Abstract: Human induced pluripotent stem cells (hiPSCs) represent an almost limitless source of cells for disease modelling and drug screening applications. Here we established an efficient and robust 3D platform for cardiomyocyte (CMs) production from hiPSCs, solely through small-molecule-based temporal modulation of the Wnt signalling, which generates more than 90% cTNT + cells. The impact of performing the differentiation process in 3D conditions as compared to a 2D culture system, was characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
72
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(78 citation statements)
references
References 59 publications
5
72
1
Order By: Relevance
“…When the RNA-sequencing data of SOTR cardiomyocytes was compared with those of adult heart cells and hiPSC-derived cardiomyocytes from a previous report 41 ( Supplementary Fig. 10), the SOTR cardiomyocytes showed lower nodal-(TBX18, SHOX2, MSX2, TBX2, HCN1, HCN4) and atrial-related (MYH6, NPPA) and higher ventricular-related (MYL2) gene expression than the previously reported cardiomyocytes 41 . Both the SOTR cardiomyocytes and cardiomyocytes of the previous study showed lower expression of MYH7 and MYL2, but higher IRX4 expression than the adult cardiomyocytes.…”
Section: And 4)mentioning
confidence: 69%
“…When the RNA-sequencing data of SOTR cardiomyocytes was compared with those of adult heart cells and hiPSC-derived cardiomyocytes from a previous report 41 ( Supplementary Fig. 10), the SOTR cardiomyocytes showed lower nodal-(TBX18, SHOX2, MSX2, TBX2, HCN1, HCN4) and atrial-related (MYH6, NPPA) and higher ventricular-related (MYL2) gene expression than the previously reported cardiomyocytes 41 . Both the SOTR cardiomyocytes and cardiomyocytes of the previous study showed lower expression of MYH7 and MYL2, but higher IRX4 expression than the adult cardiomyocytes.…”
Section: And 4)mentioning
confidence: 69%
“…They show improved myofibrillar alignment and sarcolemma remodeling which led to better Ca 2+ handling (Silbernagel et al, 2020). Moreover, hiPSC-CMs in 3D culture exhibited faster maturation analyzed by transcriptome (Branco et al, 2019), while 2D cultures hinder the maturation or cause maturation arrest (Uosaki et al, 2015).…”
Section: General Concepts Of 3d Culturementioning
confidence: 99%
“…For instance, directed differentiation towards cardiomyocytes can be induced through the early activation of the Wnt pathway, which induces mesoderm differentiation. Accordingly, the 3D aggregation of human pluripotent stem cells was found to allow faster differentiation towards the cardiac lineage through the priming of mesodermal differentiation [ 36 ]. Moreover, EB size, the composition of different substrates, and mechanical cues can enhance the differentiation of EBs into specific lineages [ 37 , 38 , 39 ].…”
Section: Molecular Changes During Embryoid Body Formationmentioning
confidence: 99%